Cyclooxygenase in Cancer Prevention and Treatments for Actinic Keratosis. Issue 1 (January 2017) - Thomas, Gareth; Morton, Colin
Abstract Non-steroidal anti-inflammatory drugs (NSAIDs) are a chemically diverse class of drugs that target the cyclooxygenase (COX) pathway and have anti-inflammatory, analgesic, and antipyretic properties. Elevated expression of COX-2 has been associated with tumor progression in skin cancer through multiple mechanisms. We present evidence for a chemoprotective effect of NSAIDs and discuss potential mechanisms of action of COX-2 in cancer. We also discuss the challenges associated with the treatment of actinic keratosis and the factors that should be taken into consideration when selecting a treatment regimen. A range of treatments are reviewed, with an emphasis on combination therapies.